Continuously adjustable narrow-band heralded single photon source - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present the high efficient generation of narrow-band heralded single photons, widely tunable in wavelength and bandwidth using resonator enhanced spontaneous down conversion in a crystalline whispering gallery mode resonator. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05